2020
DOI: 10.3892/ol.2020.11298
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings in the thyroid gland on computed tomography images of the oral and maxillofacial region

Abstract: The numbers of abnormal findings incidentally detected in adjacent regions are increasing with advances in imaging modalities. The present study aimed to examine the prevalence and characteristics of incidental findings in the thyroid gland on computed tomography (CT) images of the oral and maxillofacial region. CT scans of the oral and maxillofacial region in patients obtained between January 2012 and December 2016 were retrospectively reviewed. Images that revealed incidental findings in the thyroid gland, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated such incidental findings are present across multiple disciplines such as emergency medicine, oncology and craniofacial surgery 3,5–7 . For example, Khasawneh et al .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have demonstrated such incidental findings are present across multiple disciplines such as emergency medicine, oncology and craniofacial surgery 3,5–7 . For example, Khasawneh et al .…”
Section: Introductionmentioning
confidence: 98%
“…studied CT scans of the oral and maxillofacial regions and quantified incidental findings of the thyroid gland. The authors found that of the 1135 patients examined, 326 (28.7%) had incidental findings 5 . Thompson et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations